2013
DOI: 10.1080/01419870.2013.851397
|View full text |Cite
|
Sign up to set email alerts
|

Host-country patriotism among European immigrants: a comparative study of its individual and societal roots

Abstract: While research has traditionally focused on first-and second-generation immigrants' socio-economic incorporation and to a lesser extent on their cultural and political integration, we analyse their affective attachment to the host country. Specifically, we assess: (1) the extent to which immigrants appear more or less 'patriotic' than nonimmigrants;(2) what individual-level characteristics lead immigrants to greater (or lesser) attachment and; (3) whether cross-national differences in affective feelings toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
2
42
0
Order By: Relevance
“…First, for analysing minority group acculturation, we utilise comparable scaled measures of both national and ethnic identity that are collected independently and tap into affective but individualised dimensions of identity (Phinney 1992). We are thus able to develop previous literature exploring binary measures of national identity that may be associated with legal citizenship (Manning and Roy 2010;Platt 2014), and capture a more affective component (Reeskens and Wright 2014). We also are able to focus on identity rather than related concepts such as belonging (Burton, Nandi and Platt 2010), as used, for example by Georgiadis and Manning (2013) and Maxwell (2006), or connection to a particular country (Fisher-Neuman 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, for analysing minority group acculturation, we utilise comparable scaled measures of both national and ethnic identity that are collected independently and tap into affective but individualised dimensions of identity (Phinney 1992). We are thus able to develop previous literature exploring binary measures of national identity that may be associated with legal citizenship (Manning and Roy 2010;Platt 2014), and capture a more affective component (Reeskens and Wright 2014). We also are able to focus on identity rather than related concepts such as belonging (Burton, Nandi and Platt 2010), as used, for example by Georgiadis and Manning (2013) and Maxwell (2006), or connection to a particular country (Fisher-Neuman 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some studies have also compared minorities with majority, and these suggest that immigrant minorities' national identification is as great as that of the majority, albeit with some variation across groups (Georgiadis and Manning 2013;Karlsen and Nazroo 2013;Manning and Roy 2010;Masella 2013;Reeskens and Wright 2014). A nascent literature on generational change in identity in the UK suggests that across minority groups the tendency is for national identity to increase with time and generation, while minority identity declines (Georgiadis and Manning 2013;Guveli and Platt 2011;Platt 2014;Karlsen and Nazroo 2013;Manning and Roy 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Western Europe has found that Muslim immigrants do not always feel themselves to be a citizen of the country of settlement (Pew Project 2006). Yet, this does not mean that Muslim immigrants cannot develop a sense of belonging and commitment to the host society or adopt an adversarial stance in which this society is rejected (Reeskens and Wright 2014;Verkuyten and Yildiz 2007). Many immigrants identify not only with their minority group but also with the host society, although often not as strongly (Elkins and Sides 2007;Reeskens and Wright 2014).…”
Section: Host National Identificationmentioning
confidence: 99%
“…The rise of this issue is partially the result of escalating immigration problems encountered in the world today. For example, in their comparative study about host country patriotism among European immigrants, Tim Reeskens and Matthew Wright (2014) attempt to find out whether immigrants feel included or excluded in new situations and what contextual elements might influence them to express love and pride toward their host country. Qianqian Li's (2015) study on becoming American demonstrates how the applicants for naturalization learn American values and the reasons to be patriotic.…”
Section: From the Editorial Board Introductionmentioning
confidence: 99%